2016
DOI: 10.14569/ijacsa.2016.071206
|View full text |Cite
|
Sign up to set email alerts
|

RSECM: Robust Search Engine using Context-based Mining for Educational Big Data

Abstract: Abstract-With an accelerating growth in the educational sector along with the aid of ICT and cloud-based services, there is a consistent rise of educational big data, where storage and processing become the prime matter of challenge. Although many recent attempts have used open source framework e.g. Hadoop for storage, still there are reported issues in sufficient security management and data analyzing problems. Hence, there is less applicability of mining techniques for upcoming search engine due to unstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As indicated in [24], Machine Learning is a set of algorithms capable of learning to perform certain tasks from the generalization of examples. Machine Learning has been successfully applied to a variety of areas of human endeavor, and has recently been applied to the educational sector, whose purpose is oriented towards the design of algorithms, methods and models, which will allow the exploration of data from teaching-learning environments [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in [24], Machine Learning is a set of algorithms capable of learning to perform certain tasks from the generalization of examples. Machine Learning has been successfully applied to a variety of areas of human endeavor, and has recently been applied to the educational sector, whose purpose is oriented towards the design of algorithms, methods and models, which will allow the exploration of data from teaching-learning environments [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…The primary worry is user's secrecy and security dangers. When a person's biometric data is hijacked, the attacker can utilize it to pretend as the individual, or simply scan that individual's remote activity (Pratiba & Shobha, 2013).…”
Section: Acmentioning
confidence: 99%
“…In the sensor attacks, Latha and Rameshkumar (2013) indicated that the intruder present fake fingerprint to the sensor to produce lawful image. The impostor puts on face mask cause denial-of-service (Pratiba & Shobha, 2013). Kang, Lee, Kim, Shin and Kim (2003) applied a number of fingerprint sensors for testing and examine if the sensors can eliminate a fake fingerprint film.…”
Section: Sensor Attacksmentioning
confidence: 99%
See 1 more Smart Citation